Perlindungan Lanskap Perkebunan Tembakau Deli di Tanah Deli - Rafiqi Rafiqi; Marsella Marsella (Jurnal Ilmiah Penegakan Hukum, 2021)
Deli Tobacco is the first plantation in East Sumatra. The success of Jacobus Nienhuys in planting Deli Tobacco on Deli land. The history of plantations in East Sumatra begins. At the present time, Deli Tobacco plantations are in decline. If viewed from the history of the specialty, Deli Tobacco is a pioneer of plantations in East Sumatra. Deli Tobacco Plantation as a cultural heritage is necessary to protect and maintain the landscape. Research Objectives To determine the decline in Deli tobacco production and solutions to maintain and protect Deli Tobacco. The research method using normative juridical nature. The results of this study are Deli tobacco is a characteristic and pioneer of plantations in the land of Deli. In 1863 Jacobus Nienhuys succeeded in growing high quality cigar wrapping tobacco. However, over time Deli Tobacco production began to decline due to land occupation factors, changes in spatial planning, landscape, nationalization and social revolution. If there are no comprehensive steps, it is feared that Deli Tobacco will only remain in history according to Law No. 11 of 2010 concerning Cultural Conservation. Deli tobacco is classified as a Cultural Conservation Object, as a heritage and historical meaning